1991
DOI: 10.1038/bjc.1991.54
|View full text |Cite
|
Sign up to set email alerts
|

Expression of growth factor receptors in human brain tumours

Abstract: Summary The expression of the EGF receptor, c-erbB-2 and PDGF receptor proteins has been studied in a series of human brain tumour biopsies and cell lines. Western blotting was used to determine the amount of protein present and their intrinsic and ligand promoted enzyme activities were studied by immunoprecipitation followed by autophosphorylation. EGF receptors were found to be expressed at very high levels in 40% of primary tumour biopsies, but at uniformly low levels in tumour derived cell lines. The c-erb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

1992
1992
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 50 publications
2
19
0
1
Order By: Relevance
“…Point mutations involving codons 12, 13 and 61 of Hand K-Ras have been identi®ed in approximately 25% of human malignancies (Bos, 1989;Smith et al, 1986), although such oncogenic mutations have not been discovered in astrocytoma tumour specimens (Bos 1989;Tuzi et al, 1991) or in the established malignant human astrocytoma cell lines which we have previously characterized (U87, U118, U138, U343 and U373-MG cell lines) (Guha et al, 1997). Previous reports have demonstrated that high-grade astrocytomas (GBMs) are characterized by ampli®cation and rearrangement of the EGF-R gene (Ekstrand et al, 1994;Libermann, et al, 1984;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992), and overexpression of the PDGFRa and PDGFR-b receptors and their ligands (PDGF-A and PDGF-B), which are also functionally important in the molecular pathogenesis of these high-grade malignancies (Guha et al, 1995a,b;Shamah et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations involving codons 12, 13 and 61 of Hand K-Ras have been identi®ed in approximately 25% of human malignancies (Bos, 1989;Smith et al, 1986), although such oncogenic mutations have not been discovered in astrocytoma tumour specimens (Bos 1989;Tuzi et al, 1991) or in the established malignant human astrocytoma cell lines which we have previously characterized (U87, U118, U138, U343 and U373-MG cell lines) (Guha et al, 1997). Previous reports have demonstrated that high-grade astrocytomas (GBMs) are characterized by ampli®cation and rearrangement of the EGF-R gene (Ekstrand et al, 1994;Libermann, et al, 1984;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992), and overexpression of the PDGFRa and PDGFR-b receptors and their ligands (PDGF-A and PDGF-B), which are also functionally important in the molecular pathogenesis of these high-grade malignancies (Guha et al, 1995a,b;Shamah et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Oncogenic Ras mutations have not been discovered in human astrocytomas (Bos, 1989;Tuzi et al, 1991), which constitute the most common primary malignancy involving the central nervous system (Zimmerman, 1969). However, it has been demonstrated that high grade (grade IV) astrocytomas, known as glioblastoma multiforme (GBM), express high levels of ligand-dependent and -independent growth factor receptors (Fleming et al, 1992;Guha et al, 1995a;Libermann et al, 1984;Niste r et al, 1988;Steck et al, 1988;Sugawa et al, 1990;Wong et al, 1992) which are functionally relevant for tumour growth (Guha et al, 1995a,b;Shamah et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytomas, including GBMs, do not harbour oncogenic Ras mutations (Tuzi et al, 1991). However, we have demonstrated that the proliferation of human malignant astrocytoma cells is clearly dependent on mitogenic signals being transduced from activated receptor tyrosine kinases through the Ras signaling pathway, resulting in elevated levels of activated Ras·GTP in operative GBM tumour specimens and established astrocytoma cell lines (Guha et al, 1997).…”
mentioning
confidence: 97%
“…The activating mutations of the neu gene appear to be confined to the chemical carcinogenesis model since no such mutations have been found in human breast, thyroid, brain, stomach or pancreatic cancers (Hall et al, 1990;Lemoine et al, 1990aLemoine et al, , 1991Tuzi et al, 1991). Nevertheless, this system has revealed details of the mechanism of receptor activation which also may allow the development of selective antagonists.…”
Section: Introductionmentioning
confidence: 99%